2011
DOI: 10.3171/2011.5.jns112
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for gliomas involving the left inferior parietal lobule: new insights into the functional anatomy provided by stimulation mapping in awake patients

Abstract: To the authors' knowledge, this is the first series dedicated to the surgery of gliomas involving the left IPL. Interestingly, a certain degree of interindividual variability was observed in the distribution of the cortical maps, especially for language. Therefore, it is suggested that no rigid pattern of resection can be considered within the left IPL, and that surgery in this region should be performed in awake patients to adapt the tumor removal to individual functional limits. Nonetheless, several landmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 47 publications
5
73
3
2
Order By: Relevance
“…69,105 Lesions to this subcortical pathway have long been believed to cause conduction aphasias, although stimulation of cortical areas can also lead to the phonemic paraphasias and anomia characteristic of conduction aphasias. 1,28,64,65 Subcortical mapping studies have confirmed that the arcuate fasciculus can be accurately and reliably identified intraoperatively and that stimulation of that bundle leads to phonological errors. 28,58,64,65 Syntactical errors have also been ascribed to the arcuate fasciculus based on DTI tractography 35,38 and subcortical stimulation studies.…”
Section: Subcortical Fiber Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…69,105 Lesions to this subcortical pathway have long been believed to cause conduction aphasias, although stimulation of cortical areas can also lead to the phonemic paraphasias and anomia characteristic of conduction aphasias. 1,28,64,65 Subcortical mapping studies have confirmed that the arcuate fasciculus can be accurately and reliably identified intraoperatively and that stimulation of that bundle leads to phonological errors. 28,58,64,65 Syntactical errors have also been ascribed to the arcuate fasciculus based on DTI tractography 35,38 and subcortical stimulation studies.…”
Section: Subcortical Fiber Mappingmentioning
confidence: 99%
“…1,28,64,65 Subcortical mapping studies have confirmed that the arcuate fasciculus can be accurately and reliably identified intraoperatively and that stimulation of that bundle leads to phonological errors. 28,58,64,65 Syntactical errors have also been ascribed to the arcuate fasciculus based on DTI tractography 35,38 and subcortical stimulation studies. 107 Some question exists regarding the nomenclature of the temporoparietal tract involved in phonological processing and repetition.…”
Section: Subcortical Fiber Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a crucial role in quantity processing has been proposed for the horizontal segment of the intraparietal sulcus. With regard to electrostimulation mapping of calculation, some experiences have been reported on left parietal lobe mapping, 7,[13][14][15]21,23 while data on right parietal mapping are anecdotal and discordant. 20,25 This difference may be due to the much greater attention given to language mapping so far; however, impairment of mathematical skills can be the cause of serious personal and social difficulties.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…DES plays an important role in studies of such higher cognitive functions as hemispheric ignorance, perceptual awareness, music, calculation, memory and category-specific naming (12,(34)(35)(36)(37)(38)(39). In the present study, it was found that the Broca area of a Chinese population undergoing DES was mainly concentrated within a 1-cm range.…”
Section: Discussionmentioning
confidence: 55%